ANALISIS LENDUTAN DAN KUAT TEKAN PADA PENGUJIAN BALOK BETON BERTULANG DENGAN VARIASI JARAK SENGKANG MIRING SUDUT TEKUK 135° - Sudarno P Tampubolon; Irene Vista Simanjuntak; Priska Marlen Duakaju; SOPHIAN TALENTA MENDROFA (UKI Press, 2024)
ABSTRACT The Failure of reinforced concrte beam structures can occur due to the function of tensile reinforcement, compression reinforcement, and stirrups not functioning properly so that the beam is unable to withstand/ support the working load. This study aims to analyze the strength of reinforced concrete beams using inclined stirrups at an angle of 135° with a variation of 100 mm and 150 mm. Reinforced concrete is chosen as a combination of concrete and steel to increase the tensile strength that concrete does not have. The Ultimate Stress Design (USD) method is used to design reinforced concrete element structures. The test involved two samples of reinforced concrete beams measuring 15x15x80 cm. Based on the test, the average compressive strength of 100 mm concrete beams was 28 MPa and 150 mm was 29 MPa. The tensile test of D-13 threaded steel reinforcement produced an fy of 354 MPa and D-8 plain fy value of 369 MPa. The flexural strength of concrete beams at stirrup distances of 100 mm and 150 mm was recorded at 23.67 Mpa with a maximum deflection occurring in beam B-1 of 46.4 mm and a maximum deflection in beam B-2 of 47 mm. The results of this study provide important information about the effect of variations in inclined stirrups on the structural performance of reinforced concrete in increasing the flexural and shear strengths that occur in beams. Keywords: Reinforced Concrete, Diagonal Stirrup Reinforcement, Compressive Strength, Ultimate Stress Design (USD), Ultimate Moment Capacity, Tensile Test, Bending Strength.